An Interactive Story-Based Mobile Game Application to Diagnosing Learning Style and Learning Suggestion Based on ILS: Development and Evaluation of the Adventure Hero Game - Charoenchai Wongwatkit (2018)
© 2017 IEEE. Unknowing learning style has unavoidably become limitations for improving learning performance. Index of Learning Style (ILS) has widely been used to identify students learning style and to provide learning suggestions accordingly; unfortunately, question items are presented in text-based format, in which students may simply give responses without any careful considerations or misinterpret the questions. This could lead to misidentify their learning styles and to provide inappropriate learning tasks/activities to their preferences. Therefore, this study proposes an alternative instrument to diagnose students learning style with an interactive story-based mobile game application based on ILS. Students can interact with the scenario-based story in the game with enjoyment; meanwhile, they can make decisions by giving responses on the quest items through different situations. The quests were carefully designed and validated to ensure similar measurement to the original ILS items. Furthermore, an experiment has been conducted to evaluate its effectiveness. The findings showed that all quest items on the proposed game application are effective and reliable to diagnose students learning style and to suggest practical learning tasks/activities accordingly in lesser time in order to enhance their learning performance. In addition, students were highly satisfied and strongly accepted this novel tool; therefore, this novel game can be used as an alternative to the original ILS.